Virtual Guia Fortress: A 3D-printed eXtended Reality Playset - Chau, Iok Fong; Cardoso, Jorge C. S.; Estadieu, Gerald (Entertainment Computing – ICEC 2021, 2021)

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

(Un)Directed Reading, an interactive kiosk to encourage writing and reading - Olga Ng Ka Man, Sandra; Estadieu, Gerald; Farinha, Daniel (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
(Un)Directed Reading is an interactive installation (Edmonds, 2010) initially derived from the “Directed Reading” course, which all undergraduate students at the University must take during their final year. In this course, students are assigned different writing exercises and research assignments to open their creative and constructive minds in writing (EdwardsGroves, 2012; McVey, 2008). Every year, at the end of the course and after a selection process, a collection of stories is uploaded to a database of original stories. We then developed an open-source application to print a receipt ticket from a thermal printer with a randomly picked story every time a user pushes a button. An arcade game-style button is installed on a kiosk designed in collaboration with students and set on the university's campus (left photo). The printed receipt presents a short extract of one of the stories and a QR code that links to the full story decorated with illustrations. In a modern society where most of our interactions are audiovisual-based, young generations are less and less encouraged to read and even less to write. By offering a simple kiosk installation with short stories and graphical illustrations, we propose a new interactive interface that can easily engage passers-by to eventually stimulate their reading and creativity. By reading these stories, students, professors, staff, and visitors can be surprised by the talent of our students, as it stimulates students to write new pieces to be selected. The interactive kiosk was accessible to all for a period of 3 months with 23 stories during which we automatically collected some data to use in quantitative analysis. In this first run, we focused on data from the user's interactions such as story printed, story read, date and time. It allowed us to see the ratio between the printed receipt and the actual online reading of a story and more.

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.

Macao Soundscape as an Analysis Tool for Sound Quality Assessment - Pestana, Pedro; Barbosa, Alvaro; Estadieu, Gerald (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
Macao SAR, China is one of the more densely-populated territories in the world, and as such necessarily struggles with Soundscape quality. Nonetheless, the territory has already been identified as a unique location for to function as a Soundscape living lab (Cordeiro et al., 2014), since it has a very small manageable area that includes many types of geographical varieties, from extremely high density urban areas to natural environments with dense vegetation highland or varied water front typologies. In addition, Macao has extremely wide multicultural population with a broad range of subjects that have diverse cultural perceptions and thresholds in regards to sonic cognition. The potential impact of this diversity has already been noticed in both tourism (To & Chung, 2019) and research (Chung et al., 2016). The concept of Soundscape itself is garnering increased awareness as a viable alternative to assess the quality of the sonic environment, of use to policy management and legislation, shown not only by the increasing numbers of scientific articles on the subject (Moscoso et al., 2018), but also by recent international standardisation efforts in measuring it (ISO,2018). In this talk we shall give a preliminary description and illustration of the Soundscape in a territory that is rich in diversity and has huge potential for citizen participation. This includes approaches like noise mapping, sound mapping, Soundwalks, grounded theory efforts for detailed descriptions of the environment and use of alternative objective metrics. We will describe how to use the richness of this gathered data in developing artificial-intelligence algorithms to autonomously assess and predict the evaluation of a given Soundscape based on recordings alone. This goal will alleviate the intense human effort in subjective assessment, and may prove to be an effective and substantial diagnostics tool in planning the soundscape for prospective built environments, functioning not only as an analysis and diagnostics tool, but as a design strategy for a sustainable sonic future.

Engaging School Students with Tangible Devices: Pilot Project with .NET Gadgeteer - Thota, Neena; Estadieu, Gerald; Ferrao, Antonio; Meng, Wong Kai (2015 International Conference on Learning and Teaching in Computing and Engineering (LaTiCE), 2015)

Design Thinking Methodology and Text-To-Image Artificial Intelligence: A Case Study in the Context of Furniture Design Education - Caires, Carlos Sena; Estadieu, Gerald; Olga Ng Ka Man, Sandra (Perspectives on Design and Digital Communication IV: Research, Innovations and Best Practices, 2024)
The design thinking methodology is a problem-solving approach that involves empathising with end-users, (re)defining problems, brainstorming solutions creatively, and experimenting with prototypes and testing. It has been widely adopted in education to help students develop critical thinking, creativity, and problem-solving skills in design. On the other hand, text-to-image artificial intelligence is a method used to generate images from natural language descriptors (usually referred to as prompts). Design thinking methodology can teach students to think creatively and critically about real-world problems when applied in the classroom. In the context of design teaching at the University of Saint Joseph, Macao, students use the design thinking methodology to develop innovative proposals for furniture design solutions. Combining design thinking methodologies with text-to-image artificial intelligence can further enhance the learning experience by allowing students to generate visual representations of their ideas during the ideation phase. The authors developed a systematic approach to generate images for ideation on furniture design based on prompting text-to-image (PTI). The analysis related students’ results who applied the design thinking methodology without using AI tools and the results generated using a standard text-to-image programme. By combining both methods, teachers can help students develop critical thinking, creativity, and problem-solving skills, while also allowing them to generate visual representations in a different paradigm and, by so, being able to communicate their ideas with the most appropriate support for them.
Keywords: Artificial intelligence; Design thinking; Education quality; Furniture design education; Text-to-image prompt

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.

Book of Proceedings of ARTeFACTo2022MACAO, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities. 24-25 Nov. 2022, Macao. IEEE ISBN 979-8-3503-1004-7 - Estadieu, Gerald (2022 Third International Conference on Digital Creation in Arts, Media and Technology (ARTeFACTo), 2022)

Beyond Physical Boundaries—Organising a Virtual Exhibiton with NFTs for an International Conference - Estadieu, Gerald; Ng, S.O.K.M.; Martins de Abreu, F.; Farinha, D.F. (ARTECH 2023 - 11th International Conference on Digital and Interactive Arts, 2023)

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (ARTECH2017: Eighth International Conference on Digital Arts, 2017)

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (ACM, 2017)